Laminated Ti3SiC2/Zr based composites obtained by spark plasma sintering - Sedanova, E. P.; Murashkina, T. L.; Krotkevich, D. G.; Mingazova, Y. R.; Lider, A. M.; Travitzky, N. (Journal of Physics: Conference Series, 2021)
This paper is devoted to the fabrication of laminated Ti3SiC2/Zr based composites from Ti3SiC2 filled preceramic paper and Zr powder. The composites represented a "layers-by-layer"structure and were sintered by spark plasma at 1400 C and 50 MPa for 10-30 min. The densification behavior during the sintering, microstructure of obtained composites and influence of the holding time on the phase composition were studied.
CRIS-Team Scopus Importer:2021-08-27